SAT0565 The Expression and Regulation of the Argonaute Protein Family Member PIWIL4 in RA. (10th June 2014) - Pleštilová, L.; Aradi, B.; Filková, M.; Šenolt, L.; Ciurea, A.; Gay, R.E.; Vencovský, J.; Neidhart, M.; Gay, S.; Jüngel, A.
Abstract : Background: Aberrant expression of PIWIL (P-element induced wimpy testis like RNA-mediated gene silencing) 1-4 genes, members of the Argonaute gene family, was reported in cancer. PIWIL proteins build complexes with piwi-interacting RNAs (piRNAs) to silence gene expression. PIWIL4 is the only member of the PIWIL family, which is ubiquitously expressed in human tissues.[1] Objectives: To analyze the expression of PIWIL4 in peripheral blood mononuclear cells (PBMC) in systemic autoimmune diseases and in synovial cells from rheumatoid arthritis (RA) and osteoarthritis (OA) patients. Methods: Expression of PIWIL4 was analyzed by TaqMan RealTime-PCR in PBMC isolated from 12 RA, 7 systemic lupus erythematosus (SLE), 6 spondyloarthritis (SpA) patients, 12 healthy controls (HC), in synovial tissues and isolated synovial fibroblasts (SF) from RA and OA patients (n=5 each) and in cancer cell lines (HEK293, HeLa). RASF and OASF (n=5-12 each) were stimulated or not for 24 hours either with Poly(I:C) (10ug/ml) or LPS (5ug/ml) or TNFα (10ng/ml) and IL1β (1ng/ml). Protein expression was analyzed by Western blot. Proliferation after silencing of PIWIL4 with siRNA was assessed by cell counting. Results: In PBMC the mRNA for PIWIL4 was detected. The expression of PIWIL4 in PBMC of RA patients was significantly higher (mean dCt=2.18) than in HC (mean dCt=2.64, p<0.05), but significantly lower than in patients with SLE (mean dCt=1.42, p<0.001). There was no difference between PBMC from RA and SpA patients (mean dCt=2.30). In synovial fibroblasts from RA and OA patients, PIWIL4 could be detected. The basal expression in synovial tissues and SFs was similar in RA and OA. PIWIL4 mRNA was inducible in both RASF and OASF by Poly(I:C) 2.9-fold (p=0.003)/3.4-fold (p=0.013); LPS 2.1-fold (p=0.026)/2.6-fold (p=0.025) and TNFα in combination with IL1β 1.9-fold (p=0.003)/1.7-fold (p=0.007). The PIWIL4 transcript levels in SF were similar to that in various cancer cell lines (RASF mean dCt=4.23, HEK293 dCt=10.00, HeLa dCt=5.49), however, in comparison with cancer cells, the protein expression in SF was very low. PIWIL4 silencing decreased cell proliferation in RASF (n=5) stimulated with TNFα and IL1β (to 0.7-fold, p=0.035), but not upon stimulation with Poly(I:C) (to 0.8-fold, p=0.143). Conclusions: We have demonstrated, that PIWIL4 is present in PBMC and synovial cells from patients with RA. The induction of PIWIL4 by Toll-like receptor ligands and proinflammatory cytokines and the regulation of proliferation suggest a role of PIWIL4 in the activation of synovial fibroblasts in RA. References: Sugimoto, K., et al., The induction of H3K9 methylation by PIWIL4 at the p16Ink4a locus. Biochem Biophys Res Commun, 2007. 359(3): p. 497-502. Acknowledgements: OSTEOIMMUNE, BT Cure, TeamEU, IAR, MHCR project 023728. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3575